Animated Advertisements and Children: An Analysis of Consumer Behavior - Nasir, Faiza; Jalbani, Amanat Ali (JISR management and social sciences & economics, 2009)
This research report aims at analyzing the trend of using animations in advertisement of products specifically targeting children with special focus on selected brand examples. The researchers have assessed the impact of animated advertisements on direct and indirect consumers (children and parents) illustrating influencer-decision maker relationship and how it is manipulated by several brands for their advantage. Focus group activity was conducted in different schools (strata-wise) where inputs from both children and parents were taken. Feedback from marketers and advertisers has also been incorporated to illustrate effects over brand recall and sales of those, which have used animated advertisements. Finally, the research identifies influence of advertisement, more specifically of animated advertisements over children and their choices, their demands from parents, and overall brand recall and sales.